2024
DOI: 10.1002/esp.5789
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of five long‐term land use and management practices on runoff, soil erosion, and nutrient loss under natural rainfall in the Mollisol region of Northeast China

Qiang Chen,
Jizhen Zhang,
Mingming Guo
et al.

Abstract: Clarifying the effects of various land‐use and management practices on soil erosion and nutrient loss of sloping land can help optimize land use patterns and management strategies. This study assessed the effects of five long‐term land‐use and management practices on runoff, soil erosion, and nutrient losses. Field data from runoff plots established in 2006 in bare land (BL), natural vegetation restoration (NVR), no tillage (NT), reduced tillage (RT), and conventional tillage (CT) were used in two seasons of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 91 publications
0
0
0
Order By: Relevance
“…However, longterm conventional tillage practices (CT), such as rotary tillage and moldboard plowing, can increase soil erosion and decrease soil productivity (Bessam and Mrabet, 2003;Reicosky, 2015;Carretta et al, 2021). To address these problems, many studies have reported that conservation tillage measures, which leave at least 30% of the crop residues on the soil surface, and crop rotation can improve soil quality and control soil erosion (Farooq and Siddique, 2015;Blevins et al, 2018;Klik and Rosner, 2020;Chen et al, 2024).…”
Section: Introductionmentioning
confidence: 99%
“…However, longterm conventional tillage practices (CT), such as rotary tillage and moldboard plowing, can increase soil erosion and decrease soil productivity (Bessam and Mrabet, 2003;Reicosky, 2015;Carretta et al, 2021). To address these problems, many studies have reported that conservation tillage measures, which leave at least 30% of the crop residues on the soil surface, and crop rotation can improve soil quality and control soil erosion (Farooq and Siddique, 2015;Blevins et al, 2018;Klik and Rosner, 2020;Chen et al, 2024).…”
Section: Introductionmentioning
confidence: 99%